Principle of Freedom of Contract in the Laissez-faire Era - A. S. Ivanov (Теоретическая и прикладная юриспруденция)
The article discusses the level of development of Western European law and the operation of the principle of freedom of contract in the period of the XVIII–XIX centuries. The evolution and key changes in contractual freedom since the adoption of the laissez-faire doctrine are displayed. The author connects evolution in positive law with the transformation of the economic and socio-ethical thought of society.